Spawning, embryogenesis, settlement, and post‐settlement development of the gorgonian Plexaura homomalla - Tonra, Kaitlyn J.; Wells, Christopher D.; Lasker, Howard R. (Invertebrate biology, 2021)
Patterns of population biology and community structure can be studied by looking closely at the ontogeny and reproductive biology of reef‐building organisms. This knowledge is particularly important for Caribbean octocorals, which seem to be more resilient to long‐term environmental change than scleractinian corals and provide some of the same ecological services. We monitored the development of the black sea rod, Plexaura homomalla, a common, widely distributed octocoral on shallow Caribbean reefs, from eggs to three‐polyp colonies over the course of 10 weeks. Gametes were collected ex situ on St. John, U.S. Virgin Islands, during spawning events that occurred 3–6 days after the July full moon. Cleavage started 3.0 hr after fertilization and was holoblastic, equal, and radial. Embryos were positively buoyant until becoming planulae at 3 days after fertilization. Planulae were competent to settle 4 days after fertilization. Symbiodiniaceae began infecting polyps ~8 days after fertilization. Overall, development was typical for Caribbean octocorals, except for an increase in the number of embryos between 3.5 and 6.0 hr after fertilization.